Spatial multi-omics: deciphering technological landscape of integration of multi-omics and its applications - Liu, Xiaojie; Peng, Ting; Xu, Miaochun; Lin, Shitong; Hu, Bai; Chu, Tian; Liu, Binghan; Xu, Yashi; Ding, Wencheng; Li, Li; Cao, Canhui; Wu, Peng (Journal of hematology and oncology, 2024)
The emergence of spatial multi-omics has helped address the limitations of single-cell sequencing, which often leads to the loss of spatial context among cell populations. Integrated analysis of the genome, transcriptome, proteome, metabolome, and epigenome has enhanced our understanding of cell biology and the molecular basis of human diseases. Moreover, this approach offers profound insights into the interactions between intracellular and intercellular molecular mechanisms involved in the development, physiology, and pathogenesis of human diseases. In this comprehensive review, we examine current advancements in multi-omics technologies, focusing on their evolution and refinement over the past decade, including improvements in throughput and resolution, modality integration, and accuracy. We also discuss the pivotal contributions of spatial multi-omics in revealing spatial heterogeneity, constructing detailed spatial atlases, deciphering spatial crosstalk in tumor immunology, and advancing translational research and cancer therapy through precise spatial mapping.